사서교사의 미디어 리터러시 수업 현황과 개선 방안에 관한 연구: 고등학교 교육과정을 기반으로 - 이민희; 강봉숙; Minhui Lee; Bong-Suk Kang (Chŏngbo Kwalli Hakhoechi, 2025)
This study explores the experiences and perceptions of teacher librarians regarding media literacy education and examines ways to effectively organize it within the 2022 revised curriculum. A survey of 59 high school teacher librarians revealed the following results. Firstly, teacher librarians actively participated in media literacy education within the curriculum. And then, they proactively planned media literacy education. However, they identified insufficient instructional time as a major challenge. In addition, they demonstrated a quality of understanding regarding the high school credit system and media literacy education and recognized the significant role of school libraries and their contributions to media literacy. Furthermore, along with an integrated understanding of a curriculum such as a 'joint curriculum', the teacher librarians identified themselves as having high competency in organizing subjects. Lastly, they suggested organizing media literacy as an independent 2-credit integrated course by school year, utilizing newly developed, subject-appropriate materials. 본 연구는 사서교사의 미디어 리터러시 교육 경험과 인식을 탐구하고, 2022 개정 교육과정 내에서 미디어 리터러시 교육을 효과적으로 편성하는 방안을 모색하는 것을 목적으로 한다. 이에 전국 고등학교 사서교사 59명 대상 설문조사를 실시한 결과를 정리하면 다음과 같다. 첫째, 사서교사는 학교 교육과정 내 미디어 리터러시 교육에 적극적으로 참여하고 있었다. 둘째, 사서교사는 미디어 리터러시 교육을 적극적으로 계획하고 있었으나 교육 시간이 부족한 것을 장애 요인으로 인식하고 있었다. 셋째, 고교학점제와 미디어 리터러시 교육에 대해 매우 높은 수준의 이해도를 보였으며, 학교도서관과 사서교사가 미디어 리터러시 교육에 중요한 역할을 하고 있다고 인식하고 있었다. 넷째, '공동교육과정' 등에 종합적 이해와 함께 교과 편성에 대한 역량에 긍정적 평가를 하였다. 다섯째, 미디어 리터러시를 독립 교과로 편성할 경우 학년 단위, 2학점, 융합과목, 교과에 적합하게 새로 개발된 자료를 활용하는 것을 가장 적합하다고 인식하였다.